2022
DOI: 10.3390/ijerph191912024
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Specific Knowledge, Physical Activity, and Physical Functioning Examination among Patients with Chronic Non-Specific Low Back Pain

Abstract: Physical activity, physical functioning, and pain are some of the most critical factors of low back pain (LBP) treatment and prevention, but it was unknown that the back school program (BSP) influences the physical activity level of the patients with LBP. Data from 306 healthy patients and patients with chronic non-specific low back pain (cnsLBP) were used. We used the Global Physical Activity Questionnaire (GPAQ), the Low Back Pain Knowledge Questionnaire (LKQ), the visual analog scale, and the Roland–Morris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
2
4
2
Order By: Relevance
“…According to the physical activity guidelines for the Chinese population published in 2022 [34], our subjects met the basic physical activity requirements of 150-300 minutes of moderate intensity physical activity or 75-150 minutes of vigorous intensity physical activity per week for Chinese individuals 18 years of age and older. Interestingly, the physical activity data embodied in the population in our study differed from that of a previous Hungarian study, and they found an increase in physical activity among the people after Back School [13]. A possible explanation for this might be due to differences in lifestyle habits considering the culture and age groups of the participants.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…According to the physical activity guidelines for the Chinese population published in 2022 [34], our subjects met the basic physical activity requirements of 150-300 minutes of moderate intensity physical activity or 75-150 minutes of vigorous intensity physical activity per week for Chinese individuals 18 years of age and older. Interestingly, the physical activity data embodied in the population in our study differed from that of a previous Hungarian study, and they found an increase in physical activity among the people after Back School [13]. A possible explanation for this might be due to differences in lifestyle habits considering the culture and age groups of the participants.…”
Section: Discussioncontrasting
confidence: 95%
“…This idea is consistent with European clinical guidelines that emphasize the prevention and treatment of LBP by means of exercise and education [12]. It has been more than half a century since the Back School was proposed, but studies in different countries and populations continue to proliferate [13][14][15]. However, there are no studies related to the Chinese Back School.…”
Section: Introductionsupporting
confidence: 64%
“…In our previous BSP intervention study in Hungarian patients with cLBP, it was found that those who were educated about the LBP-specific knowledge had an increased level of physical activity, improved knowledge and understanding of the LBP, and a reduced level of disability of pain [105].…”
Section: Current Statusmentioning
confidence: 91%
“…Understanding the disease-specific aspects of LBP is crucial for preventing and treating spinal diseases [116], [117]. Some researchers have found a link between diseasespecific knowledge with effective prevention and rehabilitation [105], [118]. Therefore, knowledge of specific diseases can be developed through educational programs and measured through knowledge questionnaires.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation